Effects of Exchange Rate Volatility on Trade: Evidence from West Africa - Pabai Fofanah (Journal of Economics and Behavioral Studies, 2020)
The objective of this paper has been to investigate the impact of exchange rate volatility on trade in the context of exports, imports, and the trade balance in West Africa. Applying the pooled Ordinary Least Square, the fixed effects, and the random effect models, and obtaining robust estimates for export and trade balance models by employing xtgls, panels (correlated) Corr (ar1), and adopting xtscc, fe regression with Driscoll-Kraay standard error to estimate the import model. The empirical results show that the impact of exchange rate volatility on exports and imports is insignificant. However, the result of the trade balance model shows a positive and significant link between exchange rate volatility and the trade balance. Thus, suggesting that traders tend to engage more in export activities with an increase in exchange rate volatility. Also, the analysis suggests that depreciation of the real exchange rate will lead to a decrease in exports. Thereby, confirming the limited production capability and heavy reliance on imported goods and services. Hence, this study recommends diversification of production activities and adopting strategies aiming at reducing dependence on imported goods and services. The empirical result shows a positive association between an increase in domestic economic activities of trading partners and exports of the West African countries. This implies that West African countries must engage in trade with countries that have a high economic growth rate. The result also shows a positive link between inflation rate and imports. This suggests the implementation of effective monetary policies geared towards controlling inflation.